Chromothripsis in a case of TP53-deficient chronic lymphocytic leukemia - Pei, Jianming (Elsevier, 2012)
We describe genomic findings in a case of CLL with del(17p13.1) by FISH, in which SNP array analysis revealed chromothripsis, a phenomenon by which regions of the cancer genome are shattered and recombined to generate frequent oscillations between two DNA copy number states. The findings illustrate the value of SNP arrays for precise whole genome profiling in CLL and for the detection of alterations that would be overlooked with a standard FISH panel. This second report of chromothripsis in CLL indicates that this phenomenon is a recurrent change in this disease.